(untitled) (Proceedings of International Educators Conference, 2024)
The article examines the place where, under the influence of human consciousness and imagination, the Zarautsoy painting monument was formed in the Surkhandarya region, which is one of the first centers of human civilizations, and has preserved these artifacts created by ancient ancestors for thousands of years. years.